Persistent microfilaricidal effect of aversect combi at onchocercosis and setariosis in cattle - I. A. Arkhipov; Yu. E. Grigor’ev; A. V. Shemshura; T. S. Novik (Российский паразитологический журнал, 2016)
Persistent effect of aversect combi against microfilaria Onchocerca spp. and Setaria spp. is studied. The drug in therapeutic dose of 0,2 mg/kg showed persistence effect during 4–6 months.